DEVELOPMENT OF ELEMENTARY LINEAR ALGEBRA COURSE E-MODULES BASED ON FLIP BOOK MAKER WITH INTEGRATED ISLAMIC VALUES: PENGEMBANGAN E-MODUL MATA KULIAH ALJABAR LINEAR ELEMENTER BERBASIS FLIP BOOK MAKER YANG TERINTEGRASI NILAI-NILAI KEISLAMAN - Andi Ika Prasasti Abrar; Idah Suaidah; Sulfiani (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
The aims of this study were (1) to find out the process of developing an e-module for elementary linear algebra courses based on a flip book maker that integrates Islamic values. (2) to determine the characteristics of the e-module. (3) to determine the level of validity, practicality, and effectiveness of e-modules. The type of research used is Research and Development concerning the Plomp development model which consists of 5 stages. The product developed is an e-module course on elementary linear algebra based on a flip book maker. The test subjects in this study were second-semester students at UIN Alauddin Makassar, in the academic year 2021/2022. The instruments used were expert validation sheets, lecturer response questionnaires, observation sheets on the ability of lecturers to manage to learn, learning implementation observation sheets, student response questionnaires, student activity sheets, and learning achievement tests. Based on the trial results, it was found that (1) the product development process referred to as the Plomp development model was not fully implemented until the implementation stage due to time constraints, (2) the characteristics of the e-module are digitally designed with the flip book maker application which can be accessed using Android or Android. laptop, load learning videos, load examples of contextual questions integrated with Islamic values, and presentation of material using a scientific approach, (3) e-modules are categorized as valid with an average validity of 4.25, declared practical because all aspects are fully implemented, and declared effective because the level of completeness reached 96.3%.